1991
DOI: 10.1007/bf00202574
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition in CaGeO3 perovskite: Evidence from X-ray powder diffraction, thermal expansion and heat capacity

Abstract: Abstract. High-temperature x-ray powder diffraction study by the full pattern Rietveld method of orthorhombic CaGeO3 (Pbnm at ambient condition) perovskite confirms the previously observed phase transition at Tc = 520 K. The measured volumetric thermal expansion coefficients are 3.1 x 10 -s (K -1) below Tc and 3.5x 10 .5 (K -1) above Tc. The space group at T>Tc has been tentatively identified as Cmcm. Such a transition involves the disappearance of one of the two octahedral rotations in the (001) plane, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 20 publications
4
31
1
Order By: Relevance
“…As discussed above, Liu et al (1991) have recently suggested that CaGeO3 perovskite undergoes a firstorder transformation from its Pbnm structure to a pseudotetragonal Cmcm phase near 250 ~ C. As shown in Table 1, the distribution of Raman-active modes is similar for the Pbnm and Cmcm perovskite structures. In particular, both structures have 7 formally allowed Ag modes.…”
Section: High Temperature Vibrational Properties Of Cage03 Perovskitementioning
confidence: 71%
See 3 more Smart Citations
“…As discussed above, Liu et al (1991) have recently suggested that CaGeO3 perovskite undergoes a firstorder transformation from its Pbnm structure to a pseudotetragonal Cmcm phase near 250 ~ C. As shown in Table 1, the distribution of Raman-active modes is similar for the Pbnm and Cmcm perovskite structures. In particular, both structures have 7 formally allowed Ag modes.…”
Section: High Temperature Vibrational Properties Of Cage03 Perovskitementioning
confidence: 71%
“…As discussed in the introduction, Liu et al (1991) have proposed that CaGeO3 perovskite transforms to a Cmcm (D17h) modification above 250 ~ C. In this space group, one of the octahedral tilt angles in the ab plane vanishes, and the structure is represented by a (0 qS~b) tilting scheme. The relationship of the Cmcm structure and crystallographic directions to those for the Pbnm and cubic symmetries is displayed in Fig.…”
Section: Structure Of Cageo 3 Perovskitementioning
confidence: 98%
See 2 more Smart Citations
“…However, this behavior could be due to the tilt angles (or displacements of the oxygen atoms) being too small to produce appreciable changes in the unit cell volume. This is the case of CaGeO 3 where a Pnma to Cmcm transition seems to occur with no discontinuity in the unit cell volume (17). In fact, the Pnma-I4=mcm transition in our Fe-doped CaTiO 3 perovskites is also required by symmetry to be of first order.…”
Section: Is There An Intermediate Orthorhombic Phase?mentioning
confidence: 92%